Omission to answer, burocratic barriers and weakness in the audit as factors of vulneration to the right of petition. - Chambilla Aduviri, Isaias Samael (2020)
The objective of this investigation is to determine which are the main factors that affect the violation of the Petition Law. Tacna, 2016. The work corresponds to a non-experimental investigation (ex post facto). For this purpose, the information obtained through the questionnaire and the interview was considered. The omission of responding in writing in the legal term and illegal bureaucratic barriers by the obliged entity, and the weakness of the inspection tasks by the authorities are the main factors that affect the violation of the Petition Law. Tacna, 2016.